1996
DOI: 10.1063/1.471286
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the valence π→π* excited states of polyacenes: Benzene and naphthalene

Abstract: Multireference perturbation theory with complete active space self-consistent field ͑CASSCF͒ reference functions was applied to the study of the valence →* excited states of benzene and naphthalene. The eigenvectors and eigenvalues of CASSCF with valence active orbitals satisfy pairing properties for the alternant hydrocarbons to a good approximation. The excited states of polyacenes are classified into the covalent minus states and ionic plus states with the use of the alternancy symmetry. The present theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
157
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(189 citation statements)
references
References 63 publications
(54 reference statements)
31
157
1
Order By: Relevance
“…Similarly, different versions of the additivity rule have been applied in calculating total cross sections [33][34][35] for this scattering system. Theoretical optical oscillator strengths for the 1 E 1u electronic state have also been reported by several groups [36][37][38][39][40][41] with significant differences found between those results. As the theoretical OOS is an indication for the quality of the wavefunction used in a calculation, those differences therefore simply reflect the differing accuracy in the various wavefunctions used in those computations.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similarly, different versions of the additivity rule have been applied in calculating total cross sections [33][34][35] for this scattering system. Theoretical optical oscillator strengths for the 1 E 1u electronic state have also been reported by several groups [36][37][38][39][40][41] with significant differences found between those results. As the theoretical OOS is an indication for the quality of the wavefunction used in a calculation, those differences therefore simply reflect the differing accuracy in the various wavefunctions used in those computations.…”
Section: Introductionsupporting
confidence: 55%
“…As the theoretical OOS is an indication for the quality of the wavefunction used in a calculation, those differences therefore simply reflect the differing accuracy in the various wavefunctions used in those computations. [36][37][38][39][40][41] In Sec. II of this paper we discuss our experimental details and analysis techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also agree well with the CNDO/S-CI calculations of Swiderek et al, 21 who computed 1B 3g − , 2A g − , and 3A g − states at 5.37, 5.61, and 5.76 eV, respectively. Upon comparing our results with the MRMP and CASSCF calculations of Hashimoto et al, 16 we found that their CASSCF energies are much higher than ours, as well as compared to experimental energies, while MRMP results are comparable. Similarly, SCI results of Pariser 18 predict much higher energy differences as compared to our values.…”
Section: A Low Energy Region Of the Pa Spectrummentioning
confidence: 47%
“…Since the ground state is 1Ag, one-photon transitions to Bu states are dipoleallowed and to Ag states are dipole-forbidden in the one-photon regime, while two-photon transitions are forbidden to Bu states and allowed to Ag states. Besides the spatial symmetry, π-states can be classified according to the so-called alternacy, or particle-hole symmetry [93]. It is exact only with some model Hamiltonians (Huckel or Parriser-Parr-Pople), and becomes approximate after σ-π and second-neighbor interactions are included.…”
Section: Benchmarking Atda Study Of the Transition Dipole Momentsmentioning
confidence: 99%